ANALISIS CAPITAL ADEQUACY RATIO (CAR) DAN PENILAIAN TINGKAT KESEHATAN BANK PADA PT BANK SYARIAH XXX - Fauzi, Achmad; Marundha, Amor; Setyawan, Iwan; Syarief, Faroman; Harianto, Raden Achmad; Pramukty, Rachmat (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: Â The bank soundness rating in terms of the Capital Adequacy Ratio (CAR) is used to measure the soundness of a bank based on capital against Risk Weighted Assets (RWA). Therefore, evaluating the soundness of a bank is very important because it is useful to know the condition of the bank in a very good, good, good enough, bad or not good condition. And later it will be used by the parties concerned in making decisions. Data collection methods include the method of observation, interviews and literature study, where the discussion used is descriptive qualitative, namely the method of data analysis without using statistical methods. By looking at the case studies that occur, the focus and subfocus of research become a reference in this study. The results of the acquisition of CAR PT. Bank XXX Syariah in 2018Â Â amounted to 16.25%, in 2017 Â amounted to 15.48% and in 2018 Â amounted to 14.92%. From the results of the acquisition of CAR, it shows that PT. Bank XXX Syariah is in a state of